Formation of Professional Language Competence of Foreign Students in the Process of Teaching Architectural and Urban Terminology in the Lessons of Russian Language - M. A. Grigorieva; R. S. Satretdinova (Научный диалог, 2018)
Techniques and methods of teaching architectural and town-planning terminology at the lessons of Russian as a foreign language is presented. The authors believe that, despite the large number of works devoted to the problem of terminology, the field of architectural terminology and the language of architecture is not sufficiently studied. The article summarizes the experience of teachers of Russian Language Department of Novosibirsk state University of Architecture and Construction (sibstrin), where pedagogical techniques have been developed for many years, and textbooks and teaching materials on the formation of communicative competences in the field of professional communication for foreign students of different levels of education are published. This article examines and analyzes the complex terminological system of sub-language of architecture and urban planning. Methods of teaching foreign students of architectural direction of special vocabulary of the studied disciplines is proposed. Proposed is the model of education, which involves the acquaintance of foreign students with architectural and urban planning terms, taking into account their form, semantics and peculiarities of functioning in the scientific text. Classification of architectural and urban planning terms is presented. Productive types of tasks for independent work of foreign students are considered. The expediency of drawing up educational thematic mini-dictionaries of basic terms on the main studied disciplines is proved.